Life on the Move - Singh, Ranjit (The Trumpeter, 2024)
What does the War on Terror have to teach us about the ongoing War on Invasive Species? Rooted in the author's personal experiences as an immigrant on a family farm in Virginia, this essay explores themes of language, mental frames, and violent conflict in novel ways that shed insight into the morality of the struggle to manage unwanted species.